Molecular mechanism of Cu metal and drought stress resistance triggered by Porostereum spadiceum AGH786 in Solanum lycopersicum L. - Naz, Falak; Hamayun, Muhammad; Rauf, Mamoona; Arif, Muhammad; Afzal Khan, Sumera; Ud-Din, Jalal; Gul, Humaira; Hussain, Anwar; Iqbal, Amjad; Kim, Ho-Youn; Lee, In-Jung (Frontiers in Plant Science, 2022)
Rapid industrialization and global warming have threatened the plants with multiple abiotic stresses, such as heavy metals and drought stress. For crop cultivation, the conventional approach of cleaning the soils by excavation is very costly and not feasible for large scale. Establishing toxin-free and drought-resistant crops is a major challenge in the environment under natural and anthropogenic pressure. In the past decades, copper contamination of agricultural land has become an emerging concern. For dry land reclamation, several new strategies, including bioremediation (phytoremediation and microbial remediation), have been used. Owing to the potential of Cu hyperaccumulators, the current project aims to enhance the drought tolerance as well as the phytoremediation potential of Solanum lycopersicum L. with the inoculation of copper and 12% PEG-induced drought stress tolerant endophytic fungus P. spadiceum (AGH786) under combined stress of copper heavy metal and PEG-induced drought stress. When S. lycopersicum L. was watered with individual stress of copper (Cu) concentration (400 ppm) in the form of copper sulfate (CuSO4.5H2O), 12% PEG-induced drought stress, and combined stress of both negatively affected the growth attributes, hormonal, metabolic, and antioxidant potential compared with control. However, the multi-stress resistant AGH786 endophytic fungus ameliorated the multi-stress tolerance response in S. lycopersicum L. by positively affecting the growth attributes, hormonal, metabolic, and antioxidant potential, as well as by restricting the root-to-shoot translocation of Cu and inducing its sequestration in the root tissues of affected plants. AGH786-associated plants exhibited a reduction in the severity of the copper (Cu) and drought stress, with higher levels of SlCOPT (Cu-transporters) and SlMT (metallothionine) gene expression in root and shoot tissues, indicating that AGH786 contributed to resistance to copper metal toxicity and drought stress in the host S. lycopersicum L.